Identification of Candesartan Cilexetil-L-Arginine Co-amorphous Formation and Its Solubility Test - Fikri Alatas; Erina Sifa Mutmainah; Hestiary Ratih; Titta Hartyana Sutarna; Sundani Nurono Soewandhi (Borneo Journal of Pharmacy, 2022)
The formation of co-amorphous is one alternative that can be attempted to enhance the solubility of drugs. The study aimed to identify the co-amorphous formation between candesartan cilexetil (CAN) and l-arginine (ARG) and to know its effect on the solubility and dissolution rate of candesartan cilexetil. Initial prediction of co-crystal formation was undertaken by observing differences in crystal morphology between the candesartan cilexetil-l-arginine (CAN-ARG) mixture and each of its initial components due to crystallization in ethanol. The CAN-ARG co-amorphous was produced by the liquid-assisted grinding (LAG) method with the same molar ratio of the CAN and ARG mixture using ethanol as solvent. The co-amorphous formation of CAN-ARG was identified by powder X-ray diffraction (PXRD) and differential scanning calorimetry (DSC) methods. The solubility and dissolution test was performed to know the impact of the co-amorphous CAN-ARG formation. The PXRD pattern of CAN-ARG of LAG result showed a very low peak intensity compared to pure CAN and ARG. The DSC thermogram of the CAN-ARG LAG result does not show any sharp endothermic peaks. The PXRD and DSC results reveal that CAN and ARG can form co-amorphous. The solubility and dissolution rate of candesartan cilexetil in co-amorphous CAN-ARG was better than that of pure CAN. It can be concluded, liquid-assisted grinding of CAN-ARG mixture is identified to form co-amorphous which has an impact on increasing the solubility and dissolution rate of candesartan cilexetil.